Pengaruh Etika Bisnis Islam Terhadap Kepuasan Pelanggan (Studi Kasus UKM Holden Martabak Terang Bulan) - Jannah, Fitria Hikmatul; Indrarini, Rachma (Jurnal Ekonomika dan Bisnis Islam, 2025)
This research aims to analyze the influence of Islamic business ethics on customer satisfaction at SME Holden Martabak Terang Bulan. Islamic business ethics include the principles of honesty, justice, responsibility and concern for customers. This research uses quantitative methods with a descriptive approach. Data was collected by distributing questionnaires to SME Holden Martabak Terang Bulan customers. The data analysis technique uses simple linear regression to determine the influence of Islamic business ethics on customer satisfaction. The research results show that Islamic business ethics have a positive and significant effect on customer satisfaction. This can be seen from indicators of honesty in sales, fair product quality, responsible service, and concern for customer needs. Customer satisfaction increases along with the implementation of Islamic business ethics principles. This research provides important implications for SMEs to always apply Islamic business ethics in operational activities in order to be able to maintain customer loyalty.